Chrystologiczna interpretacja psalmów w księdze brackiej Tron królewski Jakuba Pawła Radlińskiego: wymiar teologiczny, historyczny i duchowy na tle epoki - Kot, Piotr (Verbum vitae, 2025)
The authors of the article address the question of the originality and significance of the Christological interpretation of five psalms (Ps 2; 20[19]; 45[44]; 99[98]; 110[109]) included by Fr. Jakub Paweł Radliński in his work titled The Royal Throne, published in 1735 for the needs of the Priestly Confraternity in Sanok. The book was prepared as a formation manual. For this reason, its reading prompts questions about the criteria for selecting the texts, the purpose of the Christological interpretation of the psalms, the originality of the edition in relation to other works of this type, as well as the specific theological and spiritual message it conveys. Due to the interdisciplinary nature of the research, the authors employ various methods and approaches. They begin by presenting the particular features of Radliński’s translation of the psalms in comparison with other Polish translations of the Psalter from the 14th-18th centuries. This contextual study is also important from a hermeneutical perspective, as it allows one to assess the theological correctness and the legitimacy of the Christological criterion in the translation of the psalms. Next, the psalm texts are subjected to an exegetical analysis that takes the canonical approach into account. In the next stage, the confraternity book is compared with other similar texts discovered in various libraries and archives in Poland for the purposes of the study. The use of the comparative method makes it possible to determine its historical value, biblical and theological distinctiveness, and ultimately to indicate the purpose of applying the Christological criterion in the translation of the psalms with reference to the formation of priests, who were the intended recipients of the book. The fruit of the thoughtful selection of psalms and their interpretation is the presentation of Jesus Christ as High Priest and King, an encouragement for the clergy to adopt an attitude of adoration toward Him and, as a consequence, to imitate His virtues. The emphasis on the dignity of Christ and His authority over the entire world was particularly important in the post-Reformation context, which had significantly diminished the value of the sacrament of Holy Orders.